PENGEMBANGAN MEDIA LEARNING GAME AL-QUR’AN BERBASIS MULTIMEDIA INTERAKTIF - ADE BASTIAN (Universitas Majalengka, 2020)
Madrasah Tsanawiyah (MTs) Al-Ihsan Babakanmanjeti are mostly simple learning methods such as writing on the board, reading through books, and lecture methods, especially in the method of learning to read Al-Qur'an like tajwid. The use of learning media that the authors make, namely Al-Qur'an learning games can be an alternative means for students to increase their interest in learning. The presence of Interactive multimedia-based Al-Qur'an reading media is expected to be able to attract the interest of students and the public to learn to focus more on the material being studied especially reading the Qur'an. The system development method used is a method of development using the MDLC (Multimedia Development Life Cycle) method. Questionnaires were given to teachers and students who had tried using the Al-Qur'an learning game, the questionnaire was made aimed at knowing the responses of teachers and students to the learning game. With a result of 92.7% the teacher stated that when he first tried the application it was easy to use. 96.2% of Al-Qur'an learning game teachers increase their enthusiasm for learning. And as much as 89.2% of teachers stated that the Al-Qur'an learning game provides a new atmosphere in learning. The students' responses of 99% of students stated that when they first tried the application it was easy to use. 88.3% of students stated that Al-Qur'an learning games added to the spirit of learning. And as much as 89.7% of students stated that the Al-Qur'an learning game provides a new atmosphere in learning.